Combination of Antioxidant Enzyme Overexpression and N‐Acetylcysteine Treatment Enhances the Survival of Bone Marrow Mesenchymal Stromal Cells in Ischemic Limb in Mice With Type 2 Diabetes - Qiang Zhu; Hong Hao; Huifang Xu; Yosef Fichman; Yuqi Cui; Chunlin Yang; Meifang Wang; Ron Mittler; Michael A. Hill; Peter J. Cowan; Guangsen Zhang; Xiaoming He; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Therapy with mesenchymal stem cells remains a promising but challenging approach to critical limb ischemia in diabetes because of the dismal cell survival. Methods and Results Critical limb ischemia in type 2 diabetes mouse model was used to explore the impact of diabetic limb ischemia on the survival of bone marrow mesenchymal stromal cells (bMSCs). Inhibition of intracellular reactive oxygen species was achieved with concomitant overexpression of superoxide dismutase (SOD)‐1 and glutathione peroxidase‐1 in the transplanted bMSCs, and extracellular reactive oxygen species was attenuated using SOD‐3 overexpression and N‐acetylcysteine treatment. In vivo optical fluorescence imaging and laser Doppler perfusion imaging were used to track cell retention and determine blood flow in diabetic ischemic limb, respectively. Survival of the transplanted bMSCs was significantly decreased in diabetic ischemic limb compared with the control. In vitro study indicated that advanced glycation end products, not high glucose, significantly decreased the proliferation of bMSCs and increased their apoptosis associated with increased reactive oxygen species production and selective reduction of SOD‐1 and SOD‐3. In vivo study demonstrated that concomitant overexpression of SOD‐1, SOD‐3, and glutathione peroxidase‐1, or host treatment with N‐acetylcysteine, significantly enhanced in vivo survival of transplanted bMSCs, and improved critical limb ischemia in diabetic mice. Combination of triple antioxidant enzyme overexpression in bMSCs with host N‐acetylcysteine treatment further improved bMSC survival with enhanced circulatory and functional recovery from diabetic critical limb ischemia. Conclusions Simultaneous suppression of reactive oxygen species from transplanted bMSCs and host tissue could additively enhance bMSC survival in diabetic ischemic limb with increased therapeutic efficacy in diabetes.